Conhecimento sobre energia eólica: um estudo exploratório a partir das redes semânticas naturais de estudantes da cidade de Natal - Pessoa, Viviany Silva (Universidade Federal do Rio Grande do Norte, 2008)
The human being has a fundamental role in issues concerning scarcity of energy resources as well as in the success of technologies which favor the use of renewable sources, such as wind energy. But what does wind energy mean for people? What are the psychological meanings concerning this term? Aiming to answer these questions, the general objective of this dissertation was to identify and to analyze the knowledge about wind energy taking into account a network of psychological meanings. One hundred and ninety one (191) university students from Natal-RN participated in the study, being male the majority (53%); aged between 17 and 51 years old (M=23.3 years; SD=5.7). Participants responded to self reports using the Natural Semantic Networks (NSW) technique, as well as to several sociodemographic questions. The results showed a consistent, positive and useful general semantic network. In this semantic network, knowledge about wind energy was represented by words that correspond to the appeal of (pro) environmental stance (e.g., clean and nature), that evinced both the technological aspect (e.g., force) and the economic aspect (e.g., economy). Results from different groups were also analyzed. The first set of groups (non-environemental and environmental) was divided considering the course (e.g., ecology and economy). The second set of groups(non-caretaker and caretaker) was divided based on the practice of environmental care expressed. Subtle differences were observed in the semantic networks of caretakers, who emphasized environment, an attribute not mentioned by non-caretakes. This indicates a construction of knowledge that is influenced by the presence or absence of the environmental commitment. Such findings may be useful in the construction of instruments for surveys and in the development of public and educational policies. Additionally, they may assist the media towards a more objective performance concerning wind energy
Knowledge about wind energy: an exploratory study taking into account natural semantic networks of students from Natal-RN
Keywords: Fontes renováveis de energia; Energia eólica; Psicologia ambiental; Significado psicológico; Redes semânticas naturais; Renewable energy sources; Wind energy; Environmental psychology; Psychological meaning; Natural semantic networks; CNPQ::CIENCIAS HUMANAS::PSICOLOGIA